094 Anti-NMDA receptor antibodies disrupt cortical network activity in vitro. Issue 3 (9th February 2012) - Thouin, A; Bera, K; Vincent, A; Cunningham, M O
Abstract : NMDA receptor antibody (NMDAR Ab) encephalitis is an autoimmune encephalitis causing psychiatric symptoms, amnesia, seizures, and coma. NMDAR and gamma-frequency oscillations (γ-; 20–80 Hz) both play an important role in cognitive processes and memory formation. NMDAR hypofunction and reductions in γ-oscillations have also been described in animal models of schizophrenia. We therefore hypothesise that NMDAR Abs exert an acute antagonistic action. Using an in vitro rat brain slice preparation we examined the action of NMDAR Abs on NMDA-mediated synaptic responses and persistent γ-oscillations. NMDAR Ab positive CSF (CSFNMDA) and control CSF (CSFCON) samples (n=3 and n=4, respectively) were obtained during patients' diagnostic investigations. Purified patient and control serum IgG samples were also used. There was a significant difference in the NMDA-mediated fEPSP amplitude after bath application of CSFNMDA and CSFCON (CSFCON 83.96±26.97% vs CSFNMDA 63.47±31.3% of isolated NMDA response; p<0.05, n=20 and 17 respectively). NMDAR Ab positive IgG at concentrations of 2–50 μg/ml produced a significant reduction of γ-oscillations in the entorhinal cortex (EC) (p<0.05, n=8). In contrast, in CA3 of the hippocampus γ-oscillations were not significantly altered when patient IgG was applied. In both hippocampus and EC, control patient IgG did not significantly alter γ-oscillations. The acute application of NMDAR Abs reduces NMDAR-mediated synaptic function and disrupts NMDA-dependent cortical γ-oscillations. It is therefore plausible that patients' memory and psychiatric symptoms are related to the acute pathogenic effects of NMDAR Abs on NMDAR function.